Nature’s value, philosophies, theories, and concepts: a critical review and suggestions for future indigenous research - Elizabeth Damoah; Jeffery D Connor; Kamaljit K Sangha; Bethany Cooper; Anne Poelina (Environmental Research Letters, 2024)
Numerous publications on natural resource valuations consider contexts where environmental assets at risk are significant to Indigenous Peoples and their estates. In the last two decades alone, many applied studies have aimed at investigating the ‘value’ of socio-environmental outcomes from the perspectives of the general populations including Indigenous Peoples. The term ‘value’ is often invoked in varying contexts ranging from empirical research to natural resource management (NRM) strategies and policies. Underpinning all valuation exercises is a conceptual approach to defining and analysing value, which is contextual given that different philosophies and worldviews consider nature’s ‘value’ differently. Our objective was to understand value philosophies underpinning diverse NRM ‘value’ paradigms and to evaluate compatibility with Indigenous Peoples’ value attribution. We conducted a systematic search for publications on nature studies from multiple databases using a Boolean strategy. The processes for literature identification and selection are presented in a PRISMA flowchart. The study then critically reviewed and synthesized insights from the literature on the interpretations, conceptualizations, and elicitations of value, particularly in contexts where NRM influences Indigenous estates. We found that philosophical perspectives define how ‘value’ is conceptualised and evaluated. Most studies reviewed rested on the economic paradigm grounded in anthropocentric utilitarian value-framing, and limited studies considered a relational value lens that reflects Indigenous Peoples’ value attribution for the natural environment. A relational lens sits outside of the usual ‘instrumental versus intrinsic’ value dichotomy and deems human-nature connections coupled, and worthy in themselves. The paper demonstrates the commonalities and inconsistencies across diverse value conceptualizations and describes emerging pluralistic approaches consistent with Indigenous value attribution. A novel framework for understanding and bridging the different conceptual and analytical valuation lenses, particularly on water, is presented ensuring that multiple, complex, and distinct value dimensions are empirically bridged in studies involving Indigenous Peoples.